Keteladanan Guru dalam Biografi K.H. M. Hasyim Asy’ari: Analisis Konten dan Relevansinya terhadap Pendidikan Islam Kontemporer - Ahmad Zainun Nibrasi Abu Ali; Desti Widiani; Ainun Yudhistira; Ahmad Muhammad Mustain Nasoha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to identify and analyze the exemplary values of teachers in the biography of KH. M. Hasyim Asy’ari and their relevance to contemporary Islamic education. The research employed a qualitative approach with a descriptive-analytical design through library research. Primary data sources consisted of biographies of KH. M. Hasyim Asy’ari, while secondary data were obtained from scientific journals, books, and other supporting documents. Data were collected through documentation study and analyzed using content analysis with a narrative approach. The findings reveal that the exemplary values of KH. M. Hasyim Asy’ari are classified into three main dimensions: spiritual (religiosity), personal (personal integrity), and socio-pedagogical (interpersonal). The spiritual dimension is reflected in the values of ubudiyah and muraqabah; the personal dimension includes zuhud, wara’, and istiqamah; while the socio-pedagogical dimension consists of rahmah, tawadhu’, and ‘adalah. These values are relevant to contemporary Islamic education in strengthening teachers’ character, improving professionalism, fostering a humanistic educational culture, and developing education based on Islamic values.